Long-Term Follow-up from the Treatment and Crossover Arms of a Randomized Controlled Trial of an Absorbable Nasal Implant for Dynamic Nasal Valve Collapse - Bikhazi, Nadim; Ow, Randall A.; O'Malley, Ellen M.; Perkins, Nora; Sidle, Douglas M.; Stolovitzky, Pablo (Facial Plastic Surgery, 2021)
We report the long-term safety and efficacy outcomes of the treatment and crossover arms of a randomized controlled trial evaluating an absorbable nasal implant to address dynamic nasal valve collapse. Participants were adults with severe/extreme nasal airway obstruction primarily due to nasal valve insufficiency who had implant placement. Follow-up visits were at 3, 6, 12, 18, and 24 months post implant. Visits included collection of the following patient-reported outcome measures: nasal obstructive symptom evaluation (NOSE), nasal obstruction visual analog scale (VAS), and the Epworth Sleepiness Scale (ESS). Adverse events were evaluated at each visit. One-hundred-eleven participants with implants were followed. Of the 111, 90 completed the 12-month visit and 70 completed the 24-month visit. NOSE responder rates are greater than 80% at all follow-ups through 24 months. Mean reduction from baseline in NOSE scores is ≥30 points and statistically significant (p <0.001) at all time points through 24 months. Mean VAS score reduction is ≥29.7 points and statistically significant (p <0.001) at all time points. The subgroup of participants with baseline ESS values >10 experienced statistically significant (p <0.001) and clinically meaningful reductions at all postimplant periods, suggesting that the reduction in nasal symptoms may reduce daytime sleepiness for patients who have problems with sleep quality. No serious device-/procedure-related adverse events were reported. Implant migration/retrieval rate was 4.5% (10/222) of total implants or 9% of participants (10/111). The implant is safe and effective for dynamic nasal valve collapse in patients with severe/extreme nasal obstruction and provides durable symptom improvement 24 months after placement.
Keywords: nasal valve collapse; nasal airway obstruction; bioabsorbable implant; lateral wall; nasal valve collapse